Microbiological analysis of cigarette butts and cigarette butt fibers on a tourist beach in Cartagena, Colombia (2025)
Cigarette butts (CBs) discarded on tourist beaches represent an emerging waste concern in marinecoastal ecosystems due to their persistence, low degradability, and toxicity. This study investigated CBs, cigarette butt fibers (CBFs), and beach sand in Cartagena, Colombia, as potential substrates for microbial growth. Samples were collected over five months from different beach usage zones (active, rest, and service) and analyzed for bacterial isolation, morphological and biochemical characterization, 16 S rRNA gene sequencing, and the presence of total coliforms and Escherichia coli. The results revealed the presence of both Gram-positive and Gram-negative bacteria in sand, CBs, and CBFs. Notably, Virgibacillus pantothenticus and Virgibacillus dokdonensis were identified and documented for the first time in Colombia. These findings contribute to understanding the sanitary and environmental quality of tourist beach sand and highlight potential risks to human health. Moreover, the identification of V. dokdonensis in cigarette butts discarded on beach sand is particularly relevant, as previous research suggests that certain bacterial taxa may have bioremediation potential for heavy metals.